Frankenstein - Shelley, Mary Wollstonecraft, 1797-1851 ([London] : Heinle Cengage Learning, 2007)
A monster assembled by a scientist from parts of dead bodies develops a mind of his own as he learns to loathe himself and hate his creator
Title from container
Keywords: Frankenstein (Fictitious character) -- Fiction; Monsters -- Fiction; Scientists -- Fiction; Geneva (Switzerland) -- Fiction